Investigation of Hot Pressed Polymer Electrolyte Fuel Cell Assemblies via X-ray Computed Tomography. (10th July 2017) - Meyer, Q.; Mansor, N.; Iacoviello, F.; Cullen, P.L.; Jervis, R.; Finegan, D.; Tan, C.; Bailey, J.; Shearing, P.R.; Brett, D.J.L.
Graphical abstract: Abstract: The hot pressing process for fabricating polymer electrolyte fuel cells membrane electrode assemblies (MEAs) has been widely adopted, yet little is known of its effects on the microstructural properties of the different components of the MEA. In particular, the interaction of the electrolyte, electrode and gas diffusion layer (GDL) due to lamination is difficult to probe as conventional imaging techniques cannot access the internal structure of the MEA. Here, a novel approach is used, which combines characterisation of hot-pressed membrane electrode assemblies using X-ray computed tomography, thermogravimetric analysis, differential scanning calorimetry and atomic force microscopy, with electrochemical performance measurements from polarisation curves and high-frequency impedance spectroscopy. Membrane electrode assemblies hot pressed at 100 °C, 130 °C and 170 °C reveal significant differences in microstructure, which has a consequence for the performance. When hot pressed at 100 °C, which is lower than the glass transition temperature of Nafion (123 °C), the catalyst only partially bonds with the Nafion membrane, leading to increased Ohmic resistance. At 170 °C, the Nafion membrane intrudes into the electrode, forming pinholes, degrading the catalyst layer and filling pores in the GDL. Finally, at 130 °C, the interfacial contact is optimum, with similar roughness factor between the catalyst and Nafion membrane surface, indicating effective lamination of layers.